(untitled) (Training and Practice : Journal of Educational Sciences, 2018)
The phenomenon of plant blindness is more and more wildspread in the world. People do not know the name of plants in their environment and they do not want to get familiar with them. These are the consequences of the process that we spend very little time in nature. Nowadays it can be told not only about children but about the adult generations, too. To prevent this phenomenon, parents have to work together with schools and teachers. In our work we present a survey. During that teachers’ plant knowledge was tested. They had to recognise 60 plants. Pictures were collected to show plants in their natural conditions. Plants were grouped in six groups: vegetables, fruit, cereals, the trees of the park, the flowers of the garden and herbs. Only those plants participated in the survey that could naturally be found in their environment (Vajdaság, Szerbia).